Wykluczenie posła z posiedzenia Sejmu (art. 175 ust. 5 Regulaminu Sejmu) w świetle prac Komisji Regulaminowej i Spraw Poselskich - Malec-Lewandowski, Paweł (Studia Prawa Publicznego, 2019)
This article provides an assessment of the correctness of the opinions formulated by the Rules and Deputies’ Aff airs Committee about deputies’ appeals to the Presidium of the Sejm against the Marshal of the Sejm’s decisions on their exclusions from the sittings of the Sejm. The assessment has been formulated on the basis of an analysis of the legitimacy of the arguments raised in the course of ﬁ ve sittings of the Committee. These arguments are related to problems associated with the classiﬁ cation of certain deputies’ behaviours as (i) ‘preventing conducting of the sitting’, which is the premise of deputies’ exclusion from the sitting of the Sejm, (ii) the correctness of application by the Marshal of the Sejm of the procedure leading to such exclusion and (iii) its consequences. The assessment of the correctness of the abovementioned arguments and its presentation is preceded by the description of the event occurred during the sitting of the Sejm and a reference to the content of Article 175 of the Standing Orders of the Sejm. The ﬁ rst conclusion drawn based on the analysis of the above is that the opinions issued by the Committee are correct. Another assessment concerned the legitimacy of the postulate formulated during one of the sittings of the Committee to change the body competent to recognise deputies’ appeals against the Marshal of the Sejm’s decisions on their exclusions from the sittings of the Sejm and move such competence should from the Sejm’s Presidium to the Sejm itself. The assessment of the legitimacy of that postulate has been based on the assessment of the legitimacy of the argument for such a solution, raised during the sitting in question of the Committee. The other conclusion drawn is that this postulate was legitimate.